A technology strategy to support TMC alumni engagement - Capacillo, Jules Albert B.
The Technology Management Center of UP Diliman has been in existence for the last (10) ten years and has produced over 500 graduates. Right now, the TMC has no properly organized, user-friendly database. Instead, it simply has a list of alumni names and the respective years they graduated. Also, there is no platform for facilitating interactive communications between the TMC stakeholders, particularly the alumni.